(3cJGH GdcQI hGdCSWhGfIs - (3GQTejOSs
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg hJeLjOg Efi cfJ ai WdH Gdhbha Ydi HYV GdeSGFd GdeJYOOI ai cJGH GdcQI hGdCSWhGfI dCQTejOS s
(3BNQgG (B:s
(3hNW Q M cNW Q W afSHI MQ Edi Q W cfSHI eQHY H A Edi eQHY A M hPdc eG CQOfGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHY YTQs
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1452s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs